PROSES PENERIMAAN KEHILANGAN TOKOH BAMBANG DALAM NOVEL SENDIRI KARYA TERE LIYE: PENDEKATAN PSIKOLOGI HUMANISTIK MENURUT ABRAHAM H. MASLOW - Siva; Elsa Mulya Karlina (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This research is entitled "The Process of Accepting Loss of the Character Bambang in the Novel Sendiri by Tere Liye: A Humanistic Psychology Approach According to Abraham H. Maslow. This study aims to describe and analyze the process of accepting the loss experienced by the character Bambang based on Abraham Maslow's hierarchy of needs theory, as well as to explain Bambang's journey toward self-actualization and self-acceptance after losing his life partner, viewed through the humanistic psychology perspective of Carl Rogers. The method used is a qualitative method with library research. Data sources consist of primary data, namely the novel Sendiri by Tere Liye (2024), and secondary data from supporting literature. Data were collected through reading, listening, and note-taking techniques, then analyzed using descriptive qualitative analysis with Miles and Huberman's interactive model. The results show that the loss of a life partner profoundly shook Bambang's needs at the third and fourth levels of Maslow's hierarchy. Through a long inner journey, Bambang gradually achieved psychological reconstruction toward self-actualization. From Rogers' perspective, Bambang succeeded in becoming a fully functioning person: open to experience, living existentially, and regaining trust in himself. This research demonstrates that literature can be a valid and meaningful medium for understanding the psychological dynamics of humans facing loss.